HUBUNGAN ANTARA DUKUNGAN SOSIAL KELUARGA DENGAN CRITICAL THINKING PADA SISWA SMK KRIYA SAHID DI SUKOHARJO - Zellawati, Alice; Silvia Putri, Febri (IMAGE, 2025)
This study aimed to explore the relationship between family social support and critical thinking abilities among students at SMK Kriya Sahid Sukoharjo. This quantitative research involved 111 eleventh-grade students and utilized a Likert scale for data collection on the variables of family social support and critical thinking. Data analysis using Spearman’s correlation indicated a highly significant relationship between family social support and critical thinking, with a correlation coefficient of rs=0.788 and a p-value of <0.000. The reliability test for the critical thinking scale showed a Cronbach's Alpha of 0.951, indicating a very high level of reliability. Furthermore, family social support contributed 55.6% to the variability in students' critical thinking abilities, while other factors accounted for 44.4%. This study underscores the importance of family social support in enhancing critical thinking skills, which are essential in education to prepare students for future challenges. The findings advocate for the integration of family support strategies in educational programs to maximize students' critical thinking potential. Keyword: Critical Thinking, Family Support